PENGARUH KAMPANYE PADA YOUTUBE WEB SERIES TROPICANA SLIM “SORE-ISTRI DARI MASA DEPAN” TERHADAP SIKAP GAYA HIDUP SEHAT MAHASISWA PERGURUAN TINGGI SWASTA DI KOTA BANDUNG - Siska Merdekawati; Martha Tri Lestari (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2018)
Nowadays, the digital media, especially social media gives a huge influence on the marketing world. This is where YouTube has become popular as a social media and regards as one of media platforms since many companies nowadays creating content marketing. Tropicana Slim, a company that has applied the content marketing trough YouTube in a format web series with the title